2009
DOI: 10.1007/s00441-009-0889-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered production of extra-cellular matrix components by muscle-derived Duchenne muscular dystrophy fibroblasts before and after TGF-β1 treatment

Abstract: To probe pro-fibrotic mechanisms in dystrophic muscle, we isolated primary fibroblasts from Duchenne muscular dystrophy (DMD) and control muscle biopsies and induced transdifferentiation in myofibroblasts by transforming growth factor beta1 (TGF-beta1) treatment. We compared proliferating activity, soluble collagen production, and transcript and protein levels of decorin, myostatin, TGF-beta1, matrix metalloproteinase-1 (MMP-1; interstitial collagenase), MMP-2 (gelatinase), MMP-3 (stromelysin), MMP-7 (matrilys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 60 publications
1
36
0
2
Order By: Relevance
“…However, in chronic diseases such as muscular dystrophy, fibrosis becomes self-perpetuating and excessive, inhibiting regeneration of myofibers. Several studies have suggested that dystrophic muscle fibroblasts have an increased proliferation rate and increased collagen production compared to muscle fibroblasts from normal muscle of mice and humans (Mezzano et al, 2007;Pernitsky and Anderson, 1996;Zanotti et al, 2010). Recently, we have reported that normal skeletal muscle fibroblasts express myostatin and its putative receptor, ActRIIB .…”
Section: Discussionmentioning
confidence: 93%
“…However, in chronic diseases such as muscular dystrophy, fibrosis becomes self-perpetuating and excessive, inhibiting regeneration of myofibers. Several studies have suggested that dystrophic muscle fibroblasts have an increased proliferation rate and increased collagen production compared to muscle fibroblasts from normal muscle of mice and humans (Mezzano et al, 2007;Pernitsky and Anderson, 1996;Zanotti et al, 2010). Recently, we have reported that normal skeletal muscle fibroblasts express myostatin and its putative receptor, ActRIIB .…”
Section: Discussionmentioning
confidence: 93%
“…Our previous study showed that primary fibroblasts derived from DMD muscles have a pro-fibrotic phenotype probably due to intrinsic memory of their native environment, which is altered by the primary genetic defect [54,55]. We have also shown that transcript expression and protein modulation of several ECM components are altered in DMD myotubes [58].…”
Section: Introductionmentioning
confidence: 90%
“…Control and DMD fibroblasts and myoblasts were treated with 10 ng/ml h-recombinant TGF-β1 (Peprotech EC, London, UK) for 48 h, as described previously [55].…”
Section: Muscle Biopsies and Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF- is known to modulate the ability of cells to synthesize various ECM components and was shown to modify the protein pattern produced by DMD fibroblasts upon their transformation to myofibroblasts. It increased MMP-7 thought to contribute to fibrosis (Fadic et al, 2006;Simona Zanotti et al, 2010;S. Zanotti et al, 2007).…”
Section: Matrix Metalloproteinases In Dystrophic Musclesmentioning
confidence: 99%